BUSINESS PROCESS MODELS PRESENSI BANCASSURANCE PT. ABC FINANCIAL & BANK MITRA - Kartini, Kartini; Hidayat, Ardi (JIK: Jurnal Ilmu Komputer, 2018)
AbstractBancassurance business model between PT. ABC Financial and partner banks use reference business models. The growth of insurance business, especially bancassurance in Indonesia has encouraged PT. ABC Financial to develop distribution channels through bancassurance. bancassurance can be defined as retail marketing insurance products with commercial bank client base. Distribution of insurance products through bancassurance requires the existence of an Agent or also known as Business Bancassurance from an insurance company placed in a branch office of a partner Bank to make a sale after obtaining a reference from frontliner at partner bank. The purpose of this research is to design the business process presence model to monitor the performance to meet the need for both companies for information related to bancassurance business that is placed. Using Unified Modeling Language, and SOAP technology Simple Object Access Protocol. The final results and conclusions of this study provide contributions and solutions for both companies to monitor performance in terms of their attendance levels in which they are placed in partner banks. Keywords: Bancassurance, presensi, business process models AbstrakModel bisnis bancassurance antara PT. ABC Financial dan bank mitramenggunakan model bisnis referensi. Pertumbuhan bisnis asuransi khususnya bancassurance di Indonesia telah mendorong PT. ABC Financial untuk mengembangkan jalur distribusi melalui bancassurance. bancassurance dapat didefinisikan sebagai pemasaran ritel produk asuransi dengan basis klien bank komersial. Jalur distribusi produk asuransi melalui bancassurance mensyaratkan adanya Agent atau yang dikenal juga Business Bancassurance dari perusahaan asuransi yang ditempatkan di kantor Cabang Bank mitrayang untuk melakukan penjualan setelah mendapatkan referensi dari frontliner di Bank mitra. Tujuan penelitian ini untuk mendisain model proses bisnis presensi memantau kinerja dapat memenuhi kebutuhan bagi kedua perusahaan akan informasi terkait bisnis bancassurance yang ditempatkan. Menggunakan Unified Modeling Language, dan teknologi SOAP Simple Object Access Protocol. Hasil akhir dan simpulan dari penelitian ini memberikan konstribusi dan solusi bagi kedua perusahaan untuk memantau kinerja dilihat dari tingkat kehadirannya dimana dia ditempatkan di Bank mitra. Kata kunci : Bancassurance, presensi, business process models.